THE ROLE OF DIGITAL TRANSFORMATION STRATEGY IN ENHANCING STRATEGIC POSITIONING: EVIDENCE FROM IRAQI UNIVERSITIES (World Economics and Finance Bulletin, 2025)
This research aims to identify and analyze the role of the digital transformation strategy (DTS) with its dimensions in enhancing the strategic positioning (SP) of universities. This study relies on a descriptive analytical approach by collecting data through a tool called a questionnaire and analyzing it to express the opinions of a group of lecturers at the Northern Technical University. The questionnaire was built based on a five-point Likert scale. A random sample of (285) was selected, (6) questionnaires were excluded, so the total valid for analysis was (279). The data was analyzed using SPSS 24. The study concluded that the digital transformation strategy has a high positive impact on achieving strategic positioning. Also, operational capabilities are the most influential in achieving strategic positioning within the dimensions of DTS